Compact weighted composition operators on weighted Bergman spaces - Ueki Sei-Ichiro (Acta scientiarum mathematicarum, 2009)
In this paper, we study a weighted composition operator uCv on the weighted Bergman space L2 (dA Q ) of the unit disc O. We estimate the essential norm of this type of operator. As a consequence of this estimate, we give a function-theoretic characterization of u and y that induce a compact weighted composition operator on L2(oL4Q).